Regional innovation programs' sustainability under risk and uncertainty - Liudmila Nikolova; Dmitriy Rodionov; Irina Rudskaia (Institute of Economic Research (IER), 2015)
Globalization in economy has been taking on an ever greater significance recently. Particularly important it is becoming now to such leading-edge technologies in economics as regional innovation processes. The current stage of the development of regional economies differs from the past ones in that the role of innovation programs acquires ever more importance and that forming and designing of such programs becomes now a much more independent process; all this has led to a situation where we have to revise our system of economic methods and ways of managing the risks of a regional innovation program. The existing methods and ways of risk assessment and risk management for innovations are to be complemented by new approaches reflecting the market changes and the advent of new financial instruments and stratagems. In this paper I investigate the issue of applying the system optimization method to the task of building the uncertainty/risk evaluation model for the management of a regional innovation program, proceeding from the method of limiting factor values which reduces the design value of an investment efficiency parameter to its critical limit for direct problems. As a result of my study, I propose the model of a regional innovation program's sustainability zone under risk and uncertainty, using the MATHCAT software.
Keywords: G29; 330; innovation program; region; sustainability; risk factor; system optimization